THE EFFECT OF THE RATIO OF TOFU AND OYSTER MUSHROOM TO THE CHARACTERISTICS OF OYSTER MUSHROOM NUGGETS - Ni Komang Ayu Mirah Utami Dewi; Prof.Dr. I Ketut Suter; Ni Putu Agustini, M.Si (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Indonesia is an agricultural country that has abundant natural resources, but greater human resources make natural resources not fully utilized, one of which is white oyster mushrooms (Pleurotus ostreatus) and fresh tofu dregs which are rich in nutrients and their benefits for human body. Therefore, it is necessary to diversify food using local ingredients. The purpose of this study was to study how the ratio of tofu pulp and oyster mushrooms to the characteristics of nuggets, which are made from white oyster mushrooms using tofu dregs. This research was conducted in two ways, namely preliminary research which aims to determine the function and purpose of the study and determine the boundaries and lower limits. Furthermore, the main study aimed to obtain optimal nugget formulations made from white oyster mushrooms using tofu pulp, with a group of ingredients consisting of white oyster mushrooms with 6 settings where P1 100%, P2 90%, P3 80%, P4 70% , P5 60%, P6 50%, involving tofu pulp P1 0%, P2 10%, P3 20%, P4 30%, P5 40%, P6 50%, and other ingredients are fixed variables with salt of 5 grams, pepper 2 grams, 50 gram chicken egg, 20 gram garlic, 50 gram trigu flour, 10 gram cornstarch, 10 gram panir flour. The formula predicted by this program has a protein content of 9,76; fat content 12,25; fiber content 25,76; water content 57,28, ash content 1,19, fiber content 6,92.Keywords: oyster mushrooms, oyster mushroom nuggets, tofu pulp ratio and oyster mushrooms.